2012
DOI: 10.1021/ja3038189
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Aliphatic Carbon–Carbon Bond Cleavage by a Model System of Relevance to Iron-Containing Acireductone Dioxygenase

Abstract: Mononuclear Fe(II) complexes ([(6-Ph(2)TPA)Fe(PhC(O)C(R)C(O)Ph)]X (3-X: R = OH, X = ClO(4) or OTf; 4: R = H, X = ClO(4))) supported by the 6-Ph(2)TPA chelate ligand (6-Ph(2)TPA = N,N-bis((6-phenyl-2-pyridyl)methyl)-N-(2-pyridylmethyl)amine) and containing a β-diketonate ligand bound via a six-membered chelate ring have been synthesized. The complexes have all been characterized by (1)H NMR, UV-vis, and infrared spectroscopy and variably by elemental analysis, mass spectrometry, and X-ray crystallography. Treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 42 publications
0
36
0
Order By: Relevance
“…This led us to propose a mechanistic pathway in which the Fe II center had an enhanced ability to promote the hydration of a vicinyl triketone intermediate, leading to a differentiation in regioselectivity. [22] In the current system, in the absence of water, the Ni II center has a directing effect on the chemistry, which makes this model system particularly relevant to Ni II -ARD. In terms of the reaction pathway leading to carbon-carbon bond cleavage, we note that the lack of an observed tricarbonyl intermediate (benzoylglyoxal) does not explicitly rule out the involvement of such a species.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…This led us to propose a mechanistic pathway in which the Fe II center had an enhanced ability to promote the hydration of a vicinyl triketone intermediate, leading to a differentiation in regioselectivity. [22] In the current system, in the absence of water, the Ni II center has a directing effect on the chemistry, which makes this model system particularly relevant to Ni II -ARD. In terms of the reaction pathway leading to carbon-carbon bond cleavage, we note that the lack of an observed tricarbonyl intermediate (benzoylglyoxal) does not explicitly rule out the involvement of such a species.…”
Section: Discussionmentioning
confidence: 92%
“…Notably, no evidence was found by GC-MS of a tricarbonyl-type intermediate (benzoylglyoxal) akin to that involved in reaction the reaction of complex 1 bearing the bulky acireductone 2-hydroxy-1,3-diphenylpropane-1,3-dione as ligand (Scheme 2). [22,23] In addition, no evidence was found for the formation of benzoylformic acid, which would be the expected product if only C(1)-C(2) cleavage (Fe-ARDЈ-type) reaction occurred. …”
Section: Organic Product Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent experiments and computational studies challenge this view and propose a new explanation. 69,72,73 We found that the two metals bind the substrate in the same way, exposing the same sites to the nucleophilic attack by O 2 (Figure 8) …”
Section: ■ Metal Replacement Can Also Reroutementioning
confidence: 82%